2010
DOI: 10.1186/1743-7075-7-56
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Eph receptor pathway as a novel target for eicosapentaenoic acid (EPA) modification of gene expression in human colon adenocarcinoma cells (HT-29)

Abstract: BackgroundThe health benefits of polyunsaturated fatty acids (PUFAs), particularly those of the n-3 series are well documented. The mechanisms by which these effects are mediated are not fully clarified.MethodsWe used microarrays to assess the effects on gene expression in HT29 colon adenocarcinoma cells of exposure to the n-3 fatty acid eicosapentaenoic acid (EPA). HT29 cells were cultured with EPA (150 μM) for up to 24 hr prior to harvesting and isolation of RNA. Microarray results were analyzed within the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It is very clear that lipid signalling is as yet a poorly explored area, with new insights into potential mechanisms being published on a regular basis. For example, we have recently shown that EPA can modulate the recently recognised ephrin receptor pathway, providing another route by which fish oil could protect against CRC ( 110 ) .…”
Section: Fish Consumptionmentioning
confidence: 99%
“…It is very clear that lipid signalling is as yet a poorly explored area, with new insights into potential mechanisms being published on a regular basis. For example, we have recently shown that EPA can modulate the recently recognised ephrin receptor pathway, providing another route by which fish oil could protect against CRC ( 110 ) .…”
Section: Fish Consumptionmentioning
confidence: 99%
“…Although the expression patterns of Ephs during developmental progresses have been described, the regulatory mechanism of Ephs has not been fully elucidated in stem cells [16]. A GeneGo MetaCore TM analysis of UFA-mediated signal pathways indicates that the expression of several Ephs and Ephrin ligands can be altered by UFAs [17]. Thus, it is possible that OA may alter Eph expression through the transcriptional regulation of gene expression.…”
Section: Introductionmentioning
confidence: 98%
“…MAPK signal pathway and NF-κB play important roles in the regulation of the production and activity of MMPs [10] , [19] . And many effects of IL-17A are correlated with MAPK signal pathway and NF-κB [10] , [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%